High potential in ball sports from the perspective of elite players and their youth trainers: A qualitative study - Faber, I. R.; Bustin, P. M. J.; van den Heuvel, S. C. G. H.; Oosterveld, F. G. J.; Elferink-Gemser, M. T.; Nijhuis-van der Sanden, M. W. G. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Many sports associations use talent development programs for identifying young high potential players and to support children aiming to become elite players. Selection criteria to participate in such programs are often based on performance results, coach`s judgments, physical appearance, perceptuo-motor tests for speed, agility and coordination, motivation, self-efficacy and parental support. However, identifying young children with the potential to become a world class player is a challenge, since the key factors for future success remain ambiguous. This qualitative study attempts to get a grip on what is meant by `high potential` in elite ball sports from the perspectives of world-class players and the trainers of their formative years. Methods: Semi-structured interviews were conducted in elite players (n=14; football, basketball, (beach-)volleyball, tennis, table tennis, squash, waterpolo, field-hockey) and their trainers (n=14) to unravel the multi-dimensional concept of `high potential`. After transcribing the interviews, open and axial coding was carried out by three independent coders using an inductive approach. Consecutively, all authors were involved in the peer debriefing process. Datasaturation was established. Results: The coded fragments of all interviews were reduced to seven interrelated themes describing the perspectives of the elite players and trainers with regard to high potential: `early exposure`, `deliberate play`, `fit to the sport`, `learn fast`, `taking the next step`, `constant competition` and `reaching the top of the world`. Each theme shows that high potential of a player can only be described in terms of the triptych: the player, the task (sport) and the environment. Discussion: The results of this study are consistent with the ecological-dynamic approach (Newell , 1986). Based on the results is `change over time` was added as an extra dimension to the model (Elferink-Gemser & Visscher, 2012). In addition, the results give direction to future studies that focus on the measurement of potential in young players within the framework of talent identification and development